STARTING ON THE RIGHT FOOT: DOES SCHOOL CHOICE AFFECT VETERINARIAN STARTING SALARIES?. (27th December 2016) - NEILL, CLINTON L.; HOLCOMB, RODNEY B.; BRORSEN, B. WADE
Abstract: Both schools and industry members are concerned about wages in the veterinary profession that are low relative to the years of schooling and tuition costs. This study examines the differences in starting salaries for the 2009–2014 graduates of the 28 schools accredited by the American Veterinary Medicine Association. Findings show relatively small (less than 4, 000) but statistically significant differences in starting salaries related to school choice. A larger differential effect is present among the different practice types of veterinary medicine, with equine practitioners and private industry veterinarians (e.g., pharmaceutical researchers) representing the least and greatest average starting salaries, respectively.